Bipolar highly solid-state luminescent phenanthroimidazole derivatives as materials for blue and white organic light emitting diodes exploiting either monomer, exciplex or electroplex emission. (November 2017) - Butkute, Rita; Lygaitis, Ramunas; Mimaite, Viktorija; Gudeika, Dalius; Volyniuk, Dmytro; Sini, Gjergji; Grazulevicius, Juozas Vidas
Abstract: Four phenanthroimidazole-based bipolar compounds having electron-donating carbazole or diphenylamino moieties were synthesized and characterized. All compounds form glasses and exhibit high glass transition temperatures ranging from 183 to 239 °C. Solid state blue emission was detected for all synthesized compounds and quantum yields in solid state reached 0.55. Room temperature hole and electron mobilities in the layers of phenanthroimidazole derivatives reached 3.14 × 10 −4 and 5.69 × 10 −4  cm 2 /V·s, respectively, at an electric field of 3.6 × 10 5  V/cm. Quantum chemical calculations on the molecular level were employed to interpret optical, photophysical and photoelectrical properties of the compounds. Due to the efficient blue solid-state emission and ambipolar charge transport the phenanthroimidazole-based derivatives were used for the preparation of non-doped emitting layers of blue OLEDs. The electroplex forming properties of the compounds were observed in a host:guest emitting layer with a commercial hole-transporting material 4, 4′-cyclohexylidenebis [ N, N -bis(4-methylphenyl)benzenamine]. Two most promising phenanthroimidazole-based compounds were used for the fabrication of white OLEDs which were based on both fluorescence and either electroplex or exciplex emissions. The best almost blue and white OLEDs were characterized by maximal current efficiency of 1.3 and 5.3 cd/A, power efficiency of 0.8 and 1.7 lm/W, and external quantum efficiency of 0.95 and 2.9 %. Graphical abstract: Highlights: Solid-state blue emission with quantum yields reaching 0.55. Balanced bipolar charge mobilities. Application in blue and white emitting OLEDs.